Understanding the Use of Academic Research in Science Education Practitioner Journals - Bowen, Michael; Taylor, Joseph; Patrick, Patricia; Summers, Ryan; Kubsch, Marcus; Warfa, Abdirizak; Sezen-Barrie, Asli; Guzey, Selcen; Lachapelle, Cathy (Journal of the Canadian Association for Curriculum Studies, 2020)
This bibliometric study investigated the extent to which science education practitioner journals (SEPJs) cite science education research journals and other resources, and in what proportions. The study found that articles in SEPJs rarely cite the leading science education research journals; the average citation rate per article is well below one. This result was not affected by article type and remains stable across 2013 to 2017. While results indicate the article purpose in the SEPJs affected the proportion of science education research journal citations, the proportion remains low with—in the best case—about 8% of all citations in The Science Teacher from 2013 to 2017. The presentation discusses the role of SEPJ authors of different roles/backgrounds in science education and their use of references. Implications for pedagogical content knowledge (PCK) development and the translation of research to practice are described.